Characteristics and use of draught animal power in India - Singh, Gyanendra (The Indian Journal of Animal Sciences, 2012)
Analysis was made to quantify growth and use of draught animals in Indian agriculture. It revealed that total population of bovine has increased whereas working animals population has reduced from 77.81 to 77.69 million during 1961- 62 to 1991Â·92. The analysis also revealed that male and female ratio in cattle has declined from 1.22 to 1.02 and in buffaloes from 0.39 to 0.29. The selection of implement depends upon draught power developed from the animals and therefore investigation was carried out to estimate the matrix of size distribution of draught animals. It revealed that as per their body weight, 41 % draught cattle were small and 44% medium in size. Large and heavy draught cattle comprised only 15% of the total draught cattle surveyed. Computed on the basis of weight, speed and draught matrix distribution, the weighted average draught power developed by the Indian breeds of animals was 0.24 kW. The analysis on All India basis, further revealed that, DAP use has declined from 159 to 109 animal-pair-hour per hectare (aph/ha) during 1972-91.Â